Measurements and Design Calculations for a Deep Coaxial Borehole Heat Exchanger in Aachen, Germany - Lydia Dijkshoorn; Simon Speer; Renate Pechnig (International Journal of Geophysics)
This study aims at evaluating the feasibility of an installation for space heating and cooling the building of the university in the center of the city Aachen, Germany, with a 2500 m deep coaxial borehole heat exchanger (BHE). Direct heating the building in winter requires temperatures of 40°C. In summer, cooling the university building uses a climatic control adsorption unit, which requires a temperature of minimum 55°C. The drilled rocks of the 2500 m deep borehole have extremely low permeabilities and porosities less than 1%. Their thermal conductivity varies between 2.2 W/(m·K) and 8.9 W/(m·K). The high values are related to the quartzite sandstones. The maximum temperature in the borehole is 85°C at 2500 m depth, which corresponds to a mean specific heat flow of 85 mW/m2–90 mW/m2. Results indicate that for a short period, the borehole may deliver the required temperature. But after a 20-year period of operation, temperatures are too low to drive the adsorption unit for cooling. In winter, however, the borehole heat exchanger may still supply the building with sufficient heat, with temperatures varying between 25 and 55°C and a circulation flow rate of 10 m3/h at maximum.